On the Origin of Pain – the 'Pain Channel' Hypothesis. (April 2020) - Cornish, Philip B.; Cornish, Anne P.
Abstract: Theories of pain have traditionally attributed the sensory experience of pain to the brain. We present here a new hypothesis on the origin of pain which is based on a novel approach to the management of persistent pain. We call it the 'pain channel' hypothesis of the origin of pain. There are key components to the development of our hypothesis: [1] Our clinical outcome of a persistently pain-free state, representing a maintained pain score of 0/10 has been achieved in a growing cohort of various presentations of persistent pain now exceeding 130 patients over the course of the last five years. With complete control of pain, the patients rapidly return to their premorbid state and level of function. This result requires careful consideration and explanation. [2] Regional anaesthesia has been used as a diagnostic tool to confirm the clinically suspected source of the persistent pain. The pharmacodynamics of local anaesthetics identify the sodium channel of the primary nociceptive sensory neuron as the critical subcellular structure generating pain. [3] Sodium channel function has been recognised as a bioelectromagnetic phenomenon. [4] Neuromodulation has been used to provide our long-term pain relief result. We understand the neuromodulation unit as producing an electromagnetic field within the super low wavelength range of the electromagnetic spectrum and we have devised a strategy which we believe delivers maximal electromagnetic field effect to the intended sodium channels to create a long-term conduction block. We believe that our clinical outcome challenges the current understanding of the role of the brain in pain. We hypothesise that pain is a peripheral phenomenon rather than being a construct of the brain, as our strategy is peripherally based and completely reverses the presenting clinical profile of persistent pain. More specifically we hypothesise that the sensory phenomenon of pain is a function of specific sodium channels which are coded for pain and which are part of the subcellular structure of peripheral nociceptive sensory nerves. We believe that these hypotheses can lead to a change in focus in the diagnosis and management of pain and drive improvement in current technology and medications to facilitate effective treatment of persistent pain.